CALCULATION OF GUARD SECTION FRAME SUPPORT FOR LONGERON PIPE HARDENING - Sergey A. Shamshura; Mikhail E. Popov (Advanced Engineering Research)
The checking stability calculation techniques for the guard support sections of the vibro - shock hardening stand is performed. The arched construction is accepted for the analytical model.